1974
DOI: 10.1172/jci107641
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Proteases and Cathepsin D in Human Articular Cartilage

Abstract: A B S T R A C T Proteolytic enzymes have been studied in extracts of human articular cartilage by the use of micromethods. The digestion of hemoglobin at pH 3.2 and of cartilage proteoglycan at pH 5 was shown to be due chiefly to cathepsin D. Cathepsin D was purified 900-fold from human patellar cartilage. Its identity was established by its specific cleavage of the B chain of insulin. At least six multiple forms of cathepsin D are present in cartilage; these corresponded to bovine forms 4-9. Cathepsin D had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

1975
1975
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 31 publications
4
27
0
3
Order By: Relevance
“…Methods have previously been published for the assay on a microscale of hemoglobin digestion by cathepsin D (3), and casein and histone digestion at neutral pH by cartilage extracts (6).…”
Section: Methodsmentioning
confidence: 99%
“…Methods have previously been published for the assay on a microscale of hemoglobin digestion by cathepsin D (3), and casein and histone digestion at neutral pH by cartilage extracts (6).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of enzymes on articular cartilage has been widely studied. Neutral protease (3)(4)(5)(6)(7), acid protease (4,6,(8)(9)(10), lysozyme (1 l), and collagenase (12-14) have been implicated in the erosive process. Acid protease (cathepsin D) (15) has been shown to be present in increased amounts in rheumatoid articular cartilage.…”
mentioning
confidence: 99%
“…However the possibility that chondrocytes are involved in matrix degradation cannot be ruled o u t (25).…”
Section: Discussionmentioning
confidence: 99%
“…T h e pH of the inflamed synovial exudate was again found t o be neutral, and the function of cathepsin D remains obscure. It has been suggested that its action may be confined t o intracellular digestion (25).…”
Section: Discussionmentioning
confidence: 99%